Odpowiedź :
Odpowiedź:
a) 1 i 3/5 -2 i 1/6= 1 i 18/30 - 2 i 5/30= 1 i 18/30- 1 i 35/30= - 17/30
b) 3 i 3/8 + 2 i 6/6= 3 i 3/8+ 3= 6 i 3/8
c) 1/2 - (- 1/6 -1/3)= 1/2 +1/6 +1/3= 3/6 + 1/6 + 2/6= 3/6 + 3/6= 6/6= 1
d) 7/6 + ( -5/4 -4/3)= 7/6 -5/4 -4/3= 14/12- 15/12 -16/12= 14/12- 31/12= - 17/12=
= - 1 i 5/12
e) - (- 2 i 2/3 ) + 7/15= 2 i 2/3 + 7/15= 2 i 10/15 +7/15= 2 i 17/15= 3 i 2/15
f) 1 i 5/8 - (- 2 i 2/3 + 0,25)= 1 i 5/8 + 2 i 2/3- 1/4=
= 1 i 15/24 + 2 i 16/24 - 6/24=3 i 31/24 - 6/24= 3 i 25/24= 4 i 1/24
g) 1 i 2/5 -3 i 7/8 - 0,125)= 1 i 2/5 -3 i 7/8- 1/8= 1 i 2/5- 4=
= 1 i 2/5- 3 i 5/5= -2 i 3/5
h) - 1 9/16 *11/12= - 25/16 *11/12= - 275/192= - 83/192
i) 1/2 *1/3 - ( 1/4-1/5)= 1/6- ( 5/10- 4/20)= 1/6- 1/20= 10/60- 3/60= 7/60
Szczegółowe wyjaśnienie: